2012
DOI: 10.1371/journal.pone.0034327
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effect of SRY and Its Direct Target, WDR5, on Sox9 Expression

Abstract: SRY is a sex-determining gene that encodes a transcription factor, which triggers male development in most mammals. The molecular mechanism of SRY action in testis determination is, however, poorly understood. In this study, we demonstrate that WDR5, which encodes a WD-40 repeat protein, is a direct target of SRY. EMSA experiments and ChIP assays showed that SRY could bind to the WDR5 gene promoter directly. Overexpression of SRY in LNCaP cells significantly increased WDR5 expression concurrent with histone H3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 36 publications
2
21
0
1
Order By: Relevance
“…Alternatively, decreased Gdf5 (20) and Wdr5 (26) expression, as observed in the transgenic growth plates, may also lead to downregulation of chondrocytic Sox9 expression. Recent studies have reported that WDR5 represses ␤-catenin levels (26). The highly restricted spatial distribution of the PTH2R that we observed in situ within the newborn growth plate, the increased expression of Mmp13 (3, 10) that follows PTH2R overexpression in vivo and TIP39 activation in vitro, and the decreased collagen type II immunostaining in situ implicate a role for this signaling system in the formation of the SOCs at the epiphyseal ends of the cartilaginous anlage.…”
Section: Discussionsupporting
confidence: 60%
“…Alternatively, decreased Gdf5 (20) and Wdr5 (26) expression, as observed in the transgenic growth plates, may also lead to downregulation of chondrocytic Sox9 expression. Recent studies have reported that WDR5 represses ␤-catenin levels (26). The highly restricted spatial distribution of the PTH2R that we observed in situ within the newborn growth plate, the increased expression of Mmp13 (3, 10) that follows PTH2R overexpression in vivo and TIP39 activation in vitro, and the decreased collagen type II immunostaining in situ implicate a role for this signaling system in the formation of the SOCs at the epiphyseal ends of the cartilaginous anlage.…”
Section: Discussionsupporting
confidence: 60%
“…subalbatus. SRY is a sex-determining gene, which encodes a transcription factor to trigger male development in most mammals (Berta et al, 1990;Xu et al, 2012), which is a member of the Sox (SRY-like box) gene family of DNA-binding proteins. In arthropod model organism, D. melanogaster, Sox genes are expressed in the brain, developing eye, hindgut, nervous system and testes.…”
Section: Discussionmentioning
confidence: 99%
“…Sinclair et al discovered the SRY in 1990 and they considered that SRY is the best candidate gene for the TDF [14]. Lots of studies have shown that the proteins encoded by the SRY gene play a crucial role in sex determination and differentiation [15][16][17]. DNA hybridization experiments have shown that a single hybridization band of SRY can appear in humans, chimpanzees, and some other male mammals, but does not appear in female animals.…”
Section: Discussionmentioning
confidence: 99%